THE EUROPEAN UNION ENLARGEMENT CRITERIA: THE PROMINENCE OF THE PRINCIPLE OF GOOD NEIGHBOURLINESS - Seven ERDOĞAN (Fırat University, 2019)
The European Union (EU) has always become an integration open to new members from the very beginning and there have been always some criteria that have to be met by the accession countries. As the EU evolved in time, the enlargement conditions of the Union has also changed. The eastern enlargement of the Union, which transformed a great number of post-Soviet countries into the EU members in the early 2000s, played a vital role in the current design of the enlargement process. The vast majority of the EU enlargement criteria were codified and formalised in this enlargement. This paper aims to the elaborate on one of the criteria of the EU enlargement process which is the principle of good neighbourliness. The relative importance of this principle in the EU enlargement has raised in recent years. By taking lessons from the unresolved Cyprus dispute, the EU has been trying to refrain from importing new bilateral disputes with the enlargements. Therefore, by making their solution an enlargement criteria, the EU has been paying effort to contribute to the solution of these problems before the achievement of EU membership ideal. The issue is analysed with the examples from the ongoing enlargements of the Union, which is covering Western Balkan countries and Turkey.